2007
DOI: 10.1017/s003118200700368x
|View full text |Cite
|
Sign up to set email alerts
|

Searching for general patterns in parasite ecology: host identity versus environmental influence on gamasid mite assemblages in small mammals

Abstract: The abundance and diversity of parasites vary among different populations of host species. In some host-parasite associations, much of the variation seems to depend on the identity of the host species, whereas in other cases it is better explained by local environmental conditions. The few parasite taxa investigated to date make it difficult to discern any general pattern governing large-scale variation in abundance or diversity. Here, we test whether the abundance and diversity of gamasid mites parasitic on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 30 publications
(63 reference statements)
4
51
0
3
Order By: Relevance
“…In contrast, in the highveld mole-rat, ectoparasite burdens were greatest during the wet summer (Viljoen et al, 2011), suggesting that changes in humidity rather than temperature are responsible for the observed pattern. In fact, the importance of rainfall for ectoparasites have been repeatedly shown for various taxa (Vinarski et al, 2007;Krasnov et al, 2008;Korallo-Vinarskaya et al, 2009). The winter rainfall coincides with the reproductive activity of the common mole-rat (Spinks et al, 1999); hence, the seasonal patterns observed may also be a result of a synchronized reproductive cycle between ectoparasite species and their hosts (Rothschild and Ford, 1964;Christe et al, 2000;Louren¸co and Palmeirim, 2008).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In contrast, in the highveld mole-rat, ectoparasite burdens were greatest during the wet summer (Viljoen et al, 2011), suggesting that changes in humidity rather than temperature are responsible for the observed pattern. In fact, the importance of rainfall for ectoparasites have been repeatedly shown for various taxa (Vinarski et al, 2007;Krasnov et al, 2008;Korallo-Vinarskaya et al, 2009). The winter rainfall coincides with the reproductive activity of the common mole-rat (Spinks et al, 1999); hence, the seasonal patterns observed may also be a result of a synchronized reproductive cycle between ectoparasite species and their hosts (Rothschild and Ford, 1964;Christe et al, 2000;Louren¸co and Palmeirim, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Such aggregation could have implications for the sex ratio of ectoparasite species due to the isolation of infrapopulations on individual hosts (Marshall, 1981;Poulin, 2007). The increasing isolation of such infrapopulations with decreasing ectoparasite prevalence and a resulting increased risk of inbreeding has been invoked to explain the commonly observed female bias of ectoparasites (Marshall, 1981;Matthee et al, 2007;Krasnov, 2008). In such populations, only a small number of males are required to fertilize all females, and females exhibit female-biased offspring sex ratios, resulting in reduced local mate competition (Hamilton, 1967).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations